1979
DOI: 10.1002/jcp.1040990213
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of growth and differentiation of friend murine erythroleukemia cells by 5‐bromodeoxyuridine incorporation in early S phase

Abstract: Cultured Friend murine erythroleukemia cells (Friend cells) are induced to undergo erythroid differentiation when grown in the presence of dimethylsulfoxide (DMSO) and other compounds. The effects of unifilar substitution of bromouracil (BU) for thymidine in the DNA (BU-DNA) of Friend cells were examined. Cells were grown in the presence of 5-bromodeoxy-uridine (BrdU) for one generation, then centrifuged and resuspended in medium containing DMSO without BrdU. These cells exhibited a delay in the appearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In the case of several genes induced by serum, an increase was the consequence of serum induction of quiescent cells and not of cell cycle-specific events (15,30). Proliferating cells can be separated by centrifugal-flow elutriation into size populations that are in different stages of the cell cycle (6). To study the cell cycle fluctuation of p49 mRNA in growing cells, mouse lymphoma L1210 cells were grown and separated into 10 cell-size fractions by centrifugal elutriation.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of several genes induced by serum, an increase was the consequence of serum induction of quiescent cells and not of cell cycle-specific events (15,30). Proliferating cells can be separated by centrifugal-flow elutriation into size populations that are in different stages of the cell cycle (6). To study the cell cycle fluctuation of p49 mRNA in growing cells, mouse lymphoma L1210 cells were grown and separated into 10 cell-size fractions by centrifugal elutriation.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that as cells progress through the S phase of the cell cycle, cell size increases proportionately along with nuclear DNA content (5). Therefore, we used centrifugal elutriation to sort a random population of growing cells on the basis of size into progressive intervals of the S phase, as described previously (4,6,21). Briefly, exponentially growing hybrid cells (10') or fibroblast cells (2 x 108) were pulsed with bromodeoxyuridine (BUdR; 40 and 20 ,ug/ml, respectively) for 2 to 2.5 h, after which cells were injected into the centrifugal elutriator chamber at a constant rotor (Beckman JE-1OX) speed.…”
Section: Methodsmentioning
confidence: 99%
“…Growth in the presence of BUdR, centrifugal elutriation, and flow microfluorimetric (FMF) analysis of propidium iodidestained MEL and MPC11 cells were as described previously (4)(5)(6)9). BUdR labeling and centrifugal elutnation conditions for Hepa 1.6, 22D6, 300-19P, and RL 11 were as described elsewhere (Hatton et al, in preparation; S. Stuart, F. W. Alt, and C. L. Schildkraut, manuscript in preparation).…”
Section: Methodsmentioning
confidence: 99%